Constructing identity abroad: How Chinese students in Canada reconcile their cultural identity with Western influences - Yang, Wendai; Du, Shuya (Journal of International Students, 2025)
In this paper, we investigate the phenomenon of cultural identity construction, focusing on Chinese students studying in Canada and how they deal with conflict between their Chinese and Western cultures. It investigates different factors of Western culture and examines how Chinese students construct and reconcile their identity with Western influences. The study also focuses on the psychological effects of identity reconstruction among these students. This study employed a qualitative research approach, and data were gathered through structured interviews with six Chinese students at Canadian universities. Three primary themes were revealed through thematic analysis: educational institution’s role in cultural adaptation, cultural practices and identity influence, and psychological well-being and cultural identity. Consequently, the study results show that the role of educational institutions, cultural practices, and identity conflicts significantly impact cultural adaptation and students’ psychological well-being.